Using collaborative robots to assist with travel path development for material deposition based additive manufacturing processes. Issue 4 (4th July 2018) - Djuric, Ana; Urbanic, R. Jill
ABSTRACT: Additive manufacturing process planning is in its infancy. Many new additive manufacturing platforms are being developed using a robotic based system for the positioning. It is proposed to use a collaborative robot solution to teach a 'median line' based travel path for a bead deposition based system to help with junction decision making. This input complements the model geometry and process planning settings. The logic for these tool paths is challenging algorithmically, but a process designer may have a solution in mind that it would be easier to teach; hence, integrating collaborative robots as part of the solution. Traditional robot systems require you to know the solution approach, while manual teaching involves intuition, and personal application experience. The collaborative robot is used with a designer as an intermediate step for rapid travel path development, as collaborative robots are designed for safe human-machine interactions. The designer generates path data via a collaborative robot, which is imported into process planning software. This 'proof of concept' work will be extended. The travel 'knowledge-based' data will be combined with the actual part geometry to develop a travel path using the input logic as a foundation. GRAPHICAL ABSTRACT: